The study of self adjustment, hope and satisfaction with life of ethnic groups in Indonesia - Kertamuda, Fatchiah (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the relationship between self-adjustment, hope, and life satisfaction among ethnic groups in Indonesia. The study utilizes the Self-Adjustment Scale, the Adult Hope Scale, and the Satisfaction with Life Scale among 200 participants (156 males, 44 females) currently enrolled in an internship program at an electronics company in Jakarta. The participants represent ten ethnic groups in Indonesia: Madurese (2%), Javanese (20%), Sundanese (38%), Batak (13%), Betawi (9%), Bugis (1.5%), Gorontaloan (2.5%), Minangkabau (5.5%), Malay (0.5%), and Bantenese (8%). The research presents two main findings. First, self-adjustment is influenced by life satisfaction and hope, with four predictors—ethnic group, gender, life satisfaction, and hope—contributing 5.8% to self-adjustment. Second, predictors such as ethnic group and gender contribute 0.9% to self-adjustment, while life satisfaction accounts for 1.3%, and hope (agency) contributes 3.4% to self-adjustment.